ANALISIS PUTUSAN NOMOR : 2508/Pdt.G/2022/PA.Mdn MENGENAI PEMBAGIAN HARTA WARISAN TERHADAP AHLI WARIS DALAM GUGATAN KABUR (Abscruur Libels) - Muliyati Muliyati; Akmaluddin Syahputra (LPPM Universitas Ekasakti Padang, 2023)
The division of inheritance is a very sensitive issue and there are even frequent disputes between the heirs because it relates to the dissatisfaction and selfishness of the heirs. The type of research used is normative research based on secondary data from primary, secondary and tertiary legal materials. This study analyzes the problems of implementing Decision Letter Number: 2508/Pdt.G/2022/PA.Mdn regarding the distribution of inheritance to heirs in fleeing lawsuits (Abscruur Libels). from the Compilation of Islamic Law; and the basic considerations of the Medan Islamic Religious Court judge in deciding the inheritance case Number: 2508/Pdt.G/2022/PA.Mdn with an escape lawsuit (Abscruur Libels). This study concludes that in the opinion of the plaintiff's lawsuit registered in the partnership of the Medan Religious Court Number: 2508/Pdt.G/2022/PA.Mdn contains material defects in the form of lack of parties (Plurium Litis Consortium) and blur (Abcsruur Libels). Therefore, the Panel of Judges stated that the Plaintiff's claim was unacceptable, all evidence and rebuttals as well as the final conclusions submitted by the litigants were not considered again.